2020
DOI: 10.1038/s41467-020-14576-7
|View full text |Cite
|
Sign up to set email alerts
|

Weak functional group interactions revealed through metal-free active template rotaxane synthesis

Abstract: Modest functional group interactions can play important roles in molecular recognition, catalysis and self-assembly. However, weakly associated binding motifs are often difficult to characterize. Here, we report on the metal-free active template synthesis of [2]rotaxanes in one step, up to 95% yield and >100:1 rotaxane:axle selectivity, from primary amines, crown ethers and a range of C=O, C=S, S(=O) 2 and P=O electrophiles. In addition to being a simple and effective route to a broad range of rotaxanes, the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
56
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(57 citation statements)
references
References 92 publications
(88 reference statements)
1
56
0
Order By: Relevance
“…14,38 This hypothesis was validated from FTIR analyses where hydrogen bonding between amine molecules and CEs in the presence of CE were confirmed (Figure S2). [25][26][27][28] Based on the hypothesis above, more CE molecules promoted a higher IP reaction degree as testified by XPS results in Figure S3 and Table 1. Date in Table 1 revealed that O/N ratios of modified membranes were all higher than that of the pristine membrane (N is unique to PA).…”
Section: Modification Mechanismmentioning
confidence: 79%
See 1 more Smart Citation
“…14,38 This hypothesis was validated from FTIR analyses where hydrogen bonding between amine molecules and CEs in the presence of CE were confirmed (Figure S2). [25][26][27][28] Based on the hypothesis above, more CE molecules promoted a higher IP reaction degree as testified by XPS results in Figure S3 and Table 1. Date in Table 1 revealed that O/N ratios of modified membranes were all higher than that of the pristine membrane (N is unique to PA).…”
Section: Modification Mechanismmentioning
confidence: 79%
“…On the other side, the diamine monomer (guest molecule) and the cyclic CE (host molecule) can form the host−guest inclusion F I G U R E 1 Schematic illustration of interfacial polymerization (IP) reaction between diamine and tri-acyl chloride monomers with the presence of crown ethers (CEs) [Color figure can be viewed at wileyonlinelibrary.com] complex via hydrogen-bonding interaction as shown in the Step 1 of Figure 1. [25][26][27][28] After the amidation reaction between the diamine and tri-acyl chloride monomers in IP process, the CE molecules can surround the amide bonds like the neck rings via hydrogen-bonding interaction, as shown in the Step 2 of Figure 1. 25,27,28 Ascribing to these unique characteristics of CE, we hypothesized that CE-assisted IP could significantly impact on the microstructure, morphology as well as FO performances of resulting TFC membranes.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 Takata and co-workers reported the formation of MPC enantiomers in 4.4% ee using the dynamic kinetic resolution of a pseudo-rotaxane precursor. 9a More recently, Leigh and coworkers reported a direct enantioselective synthesis of MPC rotaxanes under substrate control in an impressive 50% ee using their organocatalytic active template 11 reaction 12 in conjunction with a chiral alcohol leaving group. 9b Such direct enantioselective approaches are extremely attractive but, unless ~90% ee or higher can be achieved, the enantiomeric products still require CSP-HPLC separation for use in applications such as catalysis, 13 sensing 8,14 and materials science.…”
Section: Introductionmentioning
confidence: 99%
“…11,12 Takata and co-workers reported the formation of MPC enantiomers in 4.4% ee through the dynamic kinetic resolution of a pseudo-rotaxane precursor. 11 Leigh and co-workers recently reported a direct enantioselective synthesis of a MPC rotaxane under substrate control in an impressive 50% ee using their organocatalytic active template 13 reaction 14 in conjunction with a chiral alcohol leaving group. 12 Such direct enantioselective approaches are extremely attractive but, unless ~90% ee or higher can be achieved, the enantiomeric products still require CSP-HPLC separation for use in applications such as catalysis, 15 sensing 10,16 and materials science.…”
Section: Introductionmentioning
confidence: 99%